Green pesticide practices and sustainability: empirical insights into agricultural services in China - Yi-Feng Zhang; Yong-Hu Zhang (International Journal of Agricultural Sustainability)
In a world grappling with the overuse of pesticides, China emerges as a key consumer and producer, facing substantial challenges in environmental and agricultural sustainability. This study investigates how agricultural services can foster eco-friendly pesticide use among farmers. It leverages data from the ‘China Land Economic Survey’ (2020-2021) by Nanjing Agricultural University, covering 52 villages and 2600 households. Using a multi-dimensional fixed effects model and propensity score matching, the research addresses biases inherent in the data. Results show that agricultural business services significantly boost green pesticide adoption, outperforming agricultural technology and input sectors. These services increase the use of safer pesticides and the recycling of their containers by 11.6% and 6%, respectively. Farmer satisfaction and regular internet use also play a role in reinforcing this trend. Based on these insights, it recommends enhancing support for low-toxicity pesticides and recycling programmes, creating tailored policies for diverse agricultural needs, and implementing resource management and incentive mechanisms to promote sustainable practices. These strategies aim to bolster sustainable agriculture, balancing environmental health with economic viability.